2017
DOI: 10.1042/bcj20160480
|View full text |Cite
|
Sign up to set email alerts
|

Metal-based superoxide dismutase and catalase mimics reduce oxidative stress biomarkers and extend life span of Saccharomyces cerevisiae

Abstract: Aging is a natural process characterized by several biological changes. In this context, oxidative stress appears as a key factor that leads cells and organisms to severe dysfunctions and diseases. To cope with reactive oxygen species and oxidative-related damage, there has been increased use of superoxide dismutase (SOD)/catalase (CAT) biomimetic compounds. Recently, we have shown that three metal-based compounds {[Fe(HPClNOL)Cl]NO, [Cu(HPClNOL)(CHCN)](ClO) and Mn(HPClNOL)(Cl)}, harboring in vitro SOD and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Catalase (CAT), an enzyme found mainly in peroxisomes, can degrade hydrogen peroxide to water and oxygen and thus exert vital roles in resistance to oxidative cell injury [48]. Meanwhile, CAT inhibits the release of hydrogen peroxide into extracellular matrix and reduce oxidative stress reaction on the metal surfaces [49]. Here, Ti-NW-Zn samples obviously increased CAT expression in attached macrophages with more than fourfolds change compared to the other three surfaces (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Catalase (CAT), an enzyme found mainly in peroxisomes, can degrade hydrogen peroxide to water and oxygen and thus exert vital roles in resistance to oxidative cell injury [48]. Meanwhile, CAT inhibits the release of hydrogen peroxide into extracellular matrix and reduce oxidative stress reaction on the metal surfaces [49]. Here, Ti-NW-Zn samples obviously increased CAT expression in attached macrophages with more than fourfolds change compared to the other three surfaces (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S. cerevisiae is a suitable eukaryotic model for aging as it recapitulates the susceptibility of human cells to the proteotoxicity of α-synuclein, amyloid-β, the poliQ trait of Huntington's and mutant forms of SOD1 [180]. This model has been used to investigate the possible use of SOD mimetics as therapeutic agents against aging-related diseases, such as Parkinson's and Alzheimer's, and promising results have been obtained [286].…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…Compared to the salen-manganese complexes, the metal-based compounds have not been observed to affect the capacity of cells to synthesize neutral lipids and to compartmentalize them into lipid droplets. Cell-membrane integrity is thus maintained, hinting at possible higher efficacy against aging [286]. However, further studies that explore the real mechanism of action of these compounds must be performed to support this hypothesis.…”
Section: Sod Sourcesmentioning
confidence: 99%
“…It was demonstrated in Candida albicans that the response to nitrosative stress activates genes that regulate the expression of oxidative stress, such as catalase (Cat1), glutathione, NADPH oxidoreductase and dehydrogenase (Brown et al, 2014) elements that were identified on the proteomic analysis (Supplementary Table S1). In biological systems, cells have an antioxidant repertoire essential to ROS protection, which activates several effector molecules (Ribeiro et al, 2017).…”
Section: S-nitroso-proteome Of P Brasiliensis Under Nitrosative Stressmentioning
confidence: 99%